2008
DOI: 10.1210/en.2007-1756
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Involved in Sphingosine Kinase Activation and Sphingosine-1-Phosphate Release in Rat Myometrium in Late Pregnancy: Role in the Induction of Cyclooxygenase 2

Abstract: We investigated the regulation of the sphingosine kinase (SphK)/sphingosine-1-phosphate (S1P) axis and its role during pregnancy in the rat myometrium. SphK1 and SphK2 were coexpressed in myometrium during gestation. The levels and activity of SphK1/2 were modest at midgestation (d 12), increased at d 19 and progressively declined to low at postpartum. Similar patterns were observed for the phosphorylation of ERK and protein kinase C (PKC). Inhibition of PKC and ERK reduced SphK1/2 activity. In late pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Myometrial ERK2 phosphorylation increased significantly with advancing GA in accordance with previously reported results in the pregnant rat uterus (Oldenhof et al 2002, Serrano-Sanchez et al 2008. We observed no change in ERK1/2 phosphorylation in the myometrium with labor, which agrees with a previous report on the rat myometrium (Oldenhof et al 2002) but differs from that of Li et al (2003) who reported increased ERK2 phosphorylation in the rat uterus during labor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Myometrial ERK2 phosphorylation increased significantly with advancing GA in accordance with previously reported results in the pregnant rat uterus (Oldenhof et al 2002, Serrano-Sanchez et al 2008. We observed no change in ERK1/2 phosphorylation in the myometrium with labor, which agrees with a previous report on the rat myometrium (Oldenhof et al 2002) but differs from that of Li et al (2003) who reported increased ERK2 phosphorylation in the rat uterus during labor.…”
Section: Discussionsupporting
confidence: 92%
“…In pregnant rats, the abundance of activated ERK in myometrial cells increases with gestation (Oldenhof et al 2002, Serrano-Sanchez et al 2008 and labor onset (Li et al 2003). In animals induced to deliver preterm (PT) by administration of the progesterone receptor antagonist RU486, concurrent inhibition of ERK signaling delayed preterm labor and decreased myometrial contractility (Li et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SGPL1, thus, regulates the available pool of S1P and inhibits its signalling activities. SGPL1 may regulate S1P-induced Ptgs2 expression in the rat myometrium [32]. In this study, Sgpl1 expression increased 2.6 fold during gestation from E14.25 to E20.…”
Section: Discussionmentioning
confidence: 46%
“…Taking into account that the PTGS2/PGE2 axis plays an important role in myometrial physiology [29,50] and tumor growth [14], and that MAPK could regulate the expression of this enzyme [25][26][27], we investigated the potential role of ET-1 and subsequent MAPK3/1/MAPK14 activation in PTGS2 expression. Our data demonstrate that, in ELT3, exogenous PGE2 added in the medium induced an antiapoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that, in ELT3 cells, the sphingosine-kinase 1/sphingosine 1 phosphate (S1P) pathway contributes to the ET-1-induced antiapoptotic effect [13]. Furthermore, S1P is involved in the up-regulation of PTGS2 in late pregnant rat myometrium [50] and in ELT3 cells (data not shown). Therefore, a potential relationship between PTGS2 and S1P axis may occur in ELT3 cells.…”
mentioning
confidence: 98%